Improvement Quality Of Life In Patients With Diabetes Mellitus Type 2 - Diana Laila Ramatillah; Enrick K.E.; Agatha A.S.R.; Risa G.Y.; Sandy F.G. (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2022)
ABSTRACTDiabetes mellitus type 2 (DMT 2) is a metabolic disease caused by insulin resistance and pancreatic beta-cell dysfunction. DMT2 is ranked seventh as the 10th leading cause of death in the world and DMT2 is said to be the highest case prevalence. Patients with DMT2 must be obedient in consuming DM drugs and also pay attention to their lifestyle in order to improve their quality of life. This webinar activity was held to provide education related to treatment management for DMT2 patients and a healthy lifestyle to improve the quality of life. The webinar activity has two resource persons who are experts in their fields with 2 different materials. This webinar activity was well realized according to the success indicators with a total of 128 participants, the enthusiasm of the participants in answering questions during the quiz and the average post test results answered all the questions given with good grades.Keyword: DM Type 2, Treatment Management, Lifestyle